ANÁLISE DA ESTRUTURA E DIVERSIDADE GENÉTICA DE Paratecoma peroba (Record) Kuhlm. (BIGNONIACEAE), EM REMANESCENTES DE FLORESTA ATLÂNTICA NA REGIÃO SUL DO ESTADO DO ESPÍRITO SANTO - Franca, Tabatta Caroline Cerri (2021)
Paratecoma peroba (Record) Kuhlm, popularly known as peroba amarela is a deciduous forest species found in seasonal forests of the Atlantic Forest, reaching up 40 m in height. Wood was considered an extremely important commercial product, being used in co